Magnetic MOF for AO7 Removal and Targeted Delivery - Xue-Qing Zhan; Xiao-Yan Yu; Fang-Chang Tsai; Ning Ma; Huan-Li Liu; Yu Han; Lei Xie; Tao Jiang; Dean Shi; Yan Xiong (Crystals, 2018)
Owing to their high surface area and porosity, metal-organic frameworks (MOFs) have been gradually employed for a myriad of applications ranging from sensing, pollutant adsorption, and drug delivery to environmental remediation and catalysis. Magnetic nanoparticles-metal-organic frameworks (MMOFs) hybrid materials can facilitate facile removal of MOFs from solutions. In this report, we report the synthesis of Fe3O4@UiO-66 by encapsulation and simulated the drug loading and release by studying the adsorption and release of AO7. Thus, we loaded these MMOFs with AO7 and found that they were able to trigger and control its release by simply applying an external magnetic field. The magnetic field heats the magnets in the MOF, which causes the load to burst from the framework.